Evaluation of UAJY Learning Management System’s Usability using USE Questionnaire and Eye-tracking - Aloysius Gonzaga Pradnya Sidhawara (Indonesian Journal of Information Systems, 2022)
One of the influential learning resources utilized today is a web-based learning management system. The web-based e-learning’s usability is also influenced by the user interface. In measuring usability, eye-tracking technology can be employed to examine eye gaze of an individual when looks at a specific point at a certain time. The use of eye-tracking is beneficial in obtaining objective data. This study aims to evaluate the usability of UAJY Learning Management System website interface and examine the user's interaction with the website interface. Thirty-five participants were recruited in a usability testing experiment. Participants were asked to do three tasks related to the use of e-learning features while their eye movements were recorded. The USE Questionnaire and task-related question data were processed using statistical descriptive methods and eye movement data generated into heatmaps. The Usefulness, Ease of Use, Ease of Learn, and Satisfaction aspects of the UAJY LMS gains more than 80% feasibility percentage. Overall results of feasibility categorized the UAJY LMS as Very Feasible. There was no difference found in usability aspects between gender, faculty background, and eye condition groups. Heatmaps results show that navigational elements in the LMS are utilized properly and successfully help participants in performing tasks.